Experimental study on waste tyre rubber reinforced concrete - Vadivel, T. Senthil; Thenmozhi, R.; Doddurani, M. (Journal of Structural Engineering, 2024)
The main objective of solid waste management system is to effectively safeguard the public health, safety and welfare. Recycled materials are mostly used for non load bearing structures. Nevertheless, large numbers of industrial and municipal wastes can be utilized in the building industry. This paper focuses on existing practices related to the reuse of waste tyre rubber and identifies new potential use. The development of new construction material using recycled waste tyre is important to both the construction industry and rubber industry. Extensive research has been carried out to investigate the use of waste tyre rubber as reinforcement in under reinforced beams. 14 numbers of beams were cast with 2 numbers of 15mm × 25mm size scrap tyre rubber as reinforcement instead of steel in tension zone. The experiments were carried out to determine the flexural behavior of tyre reinforced concrete beam in different ages. It was found that all the test specimens behaved in a ductile manner and testing proceeded in a smooth and controlled way. Based on the experiment measurements, the ultimate strength, flexural stiffness and ductility are analyzed and compared. The test results also indicate that strength and stiffness of the beam are comparable to Reinforced Concrete beams.